Estudo do perfil imunológico de subpopulações de células T naive e de memória em pacientes convalescentes da covid-19 - Peixoto, Rephany Fonseca (2023)
COVID-19 is a severe acute respiratory infection caused by the SARS-CoV-2 virus capable of suffering from different clinical conditions ranging from asymptomatic to severe, in which the host's immune response is crucial for its establishment. Long-lived SARS-CoV-2- specific CD4+ and CD8+ memory T cells are essential for long-term immune protection against COVID-19 as they have an increased ability to restrict viral replication in a secondary infection. Thus, the present study aims to investigate immunomodulatory mechanisms mediated by CD4+ and CD8+ T lymphocyte subtypes in patients who recovered from mild and severe forms of COVID-19 before vaccination by flow cytometry. Thus, peripheral blood samples were obtained from recruited volunteers and distributed into control (CTL - n = 9), mild (n =9), and severe (n = 6) groups. Samples of PBMCs were obtained and incubated under 3 different conditions: unstimulated (medium), and stimulated with SARSCoV-2 peptides (Pool Spike CoV-2 and Pool CoV-2. CD4+ and CD8+ T cells were analyzed and classified for CCR7+ and CD45RA+ expression in naive CD4+/CD8+ T cells (TN), CD4+/CD8+ central memory T cells (TMC), CD4+/CD8+ effector memory T cells (TME), and CD4+/CD8+ effector memory T cells that reexpress CD45RA (TMERA). Thus, in the different subpopulations mentioned above, cytokines (IL-10, IFN-y, TNF-α, and IL-17) and activation markers (CD69, CD137, and Ki67) were expressed analyzed by flow cytometry. Pool Spthe ike CoV-2 and Pool CoV-2 stimulus elicited a higher frequency of CD8+ TCM cells and CD4+ TEMRA cells in recovered mild group. CD4+ and CD8+ TCM and TEM cells showed heterogeneity in CD137 and CD69 activation marker expressions between mild and severe recovered groups. Also, we observed a predominance in CD137 expression by naive CD4+ and CD8+ cells, TCM, and TEM from the mild recovered group when stimulated with antigenic pools. Additionality, a higher CD69 expression from the severe recovered group by CD4+ and CD8+ TEMRA cells was observed under SARS-CoV-2 Epitope Pools. CD4+ and CD8+ naïve, TCM and TEM cells subsets from recovered mild volunteers had higher expression of TNF-α while the expression partner of IFN-γ, IL-10, and IL-17 point to an antiviral signature by TEMRA CD8+ cells. Our findings contribute to the elucidation of the functional capabilities of each subpopulation of memory T cells during SARS CoV-2 antigenic reexposure, as well as their role in disease outcome in individuals recovered from COVID-19.